1988
DOI: 10.1007/bf02555145
|View full text |Cite
|
Sign up to set email alerts
|

A monoclonal antibody against dentin phosphophoryn recognizes a bone protein(s) appearing at the beginning of ossification

Abstract: Decalcified and nondecalcified sections of fetal bovine tibia were stained immunohistochemically with a monoclonal antibody against dentin phosphophoryn. In the epiphyseal portion of the long bone, osteoblasts, osteocytes and the bone matrix were stained, but chondrocytes and the cartilage matrix were not. Similar staining was observed in the epiphyseal and diaphyseal portions of bones. These findings suggest that a protein(s) with the same epitope as phosphophoryn may be synthesized and secreted by osteoblast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…The presence of phosphophoryn has not yet been reported in other tissues. Although Nakama et al (1988) reported the presence of bone proteins which are immunoreactive with an antibody raised against phosphophoryn, these proteins are distinctly different from phosphophoryn.…”
Section: Introductionmentioning
confidence: 90%
“…The presence of phosphophoryn has not yet been reported in other tissues. Although Nakama et al (1988) reported the presence of bone proteins which are immunoreactive with an antibody raised against phosphophoryn, these proteins are distinctly different from phosphophoryn.…”
Section: Introductionmentioning
confidence: 90%